Outcomes of patients after successful left ventricular assist device explantation: a EUROMACS study - Antonides, Christiaan F J; Schoenrath, Felix; de By, Theo M M H; Muslem, Rahatullah; Veen, Kevin; Yalcin, Yunus C; Netuka, Ivan; Gummert, Jan; Potapov, Evgenij V; Meyns, Bart; Özbaran, Mustafa; Schibilsky, David; et al. (ESC heart failure, 2020)
AIMS: Sufficient myocardial recovery with the subsequent explantation of a left ventricular assist device (LVAD) occurs in approximately 1-2% of the cases. However, follow-up data about this condition are scarcely available in the literature. This study aimed to report the long-term outcomes and clinical management following LVAD explantation. METHODS AND RESULTS: An analysis of the European Registry for Patients with Mechanical Circulatory Support was performed to identify all adult patients with myocardial recovery and successful explantation. Pre-implant characteristics were retrieved and compared with the non-recovery patients. The follow-up data after explantation were collected via a questionnaire. A Kaplan-Meier analysis for freedom of the composite endpoint of death, heart transplantation, LVAD reimplantion, or heart failure (HF) relapse was conducted. A total of 45 (1.4%) cases with myocardial recovery resulting in successful LVAD explantation were identified. Compared with those who did not experience myocardial recovery, the explanted patients were younger (44 vs. 56 years, P < 0.001), had a shorter duration of cardiac disease (P < 0.001), and were less likely to have ischaemic cardiomyopathy (9% vs. 41.8%, P < 0.001). Follow-up after explantation could be acquired in 28 (62%) cases. The median age at LVAD implantation was 43 years (inter-quartile range: 29-52), and 23 (82%) were male. Baseline left ventricular ejection fraction was 18% (inter-quartile range: 10-20%), and 60.7% of the patients had Interagency Registry for Mechanically Assisted Circulatory Support Profile 1 or 2. Aetiologies of HF were dilated cardiomyopathy in 36%, myocarditis in 32%, and ischaemic in 14% of the patients, and 18% had miscellaneous aetiologies. The devices implanted were HeartMate II in 14 (50%), HVAD in 11 (39%), HeartMate 3 in 2 (7%), and 1 unknown with a median duration of support of 410 days (range: 59-1286). The median follow-up after explantation was 26 months (range 0.3-73 months), and 82% of the patients were in New York Heart Association Class I or II. Beta-blockers were prescribed to 85%, angiotensin-converting enzyme inhibitors to 71%, and loop diuretics to 50% of the patients, respectively. Freedom from the composite endpoint was 100% after 30 days and 88% after 2 years. CONCLUSIONS: The survival after LVAD explantation is excellent without the need for heart transplantation or LVAD reimplantation. Only a minority of the patients suffer from a relapse of significant HF.
Keywords: tepový objem; Humans; Heart Failure; Stroke Volume; srdeční selhání; funkce levé komory srdeční; Mechanical circulatory support; Female; dospělí; Survival; výsledek terapie; lidé; Left ventricular assist device; Myocardial recovery; Adult; podpůrné srdeční systémy; ženské pohlaví; Male; Explantation; Treatment Outcome; Heart-Assist Devices; mužské pohlaví; Ventricular Function, Left